The viewpoint from psychology: Attitudinal impact of young adults’ intention on retail equity participation - Chong, Thim Kit; Yap, Felicia Jia Yi; Lim, Xin Yi; Teen, Jia Jia (2023)
To investigate how attitudinal factors influence Malaysian young adults’ intention to participate in the stock market, a study was conducted on the relationship between investment intention and several attitudinal factors. The study involved 253 respondents who participated online and used Partial Least Squares Structural Equation Modeling (PLS-SEM) to obtain statistical results such as Cronbach's alpha, composite reliability, average variance extracted (AVE), discriminant validity, and hypothesis testing. The study found that social influence and risk avoidance had a significant relationship to Malaysian young adults’ intention to invest into the stock market, while hassle factors and financial well-being were not. The research discovered that individuals who are cautious about taking risks and are uncomfortable with uncertainty are less inclined to invest in the stock market. On the other hand, those who are comfortable with risk and uncertainty are more likely to invest. The studies also found that individual often seek information from their social network when making investment decisions, and the recommendations they receive from family, friends, and colleagues can directly impact their decision to invest in the stock market. Finally, this research offers insights and recommendations to various parties including Bursa participating organizations, Bursa Malaysia, Securities Commission Malaysia, scholars, and researchers.